Integration Of The Communicative Method With Digital Technologies In Teaching The German Language - Ruzieva, Mahbuba Islamovna (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article examines the theoretical and practical aspects of integrating the communicative method with digital technologies in teaching the German language. The results show that the synthesis of the communicative method and digital technologies significantly develops students’ oral and written skills, increases motivation, and expands the possibilities of independent learning.